Kinetic study of electrocoagulation of tannery wastewater - Valdiviezo Gonzales, Lorgio Gilberto (2023)
The current research aims to investigate the treatment of real chrome tanning effluent by continuing electrocoagulation (EC) with electrodes of aluminum (anode) and iron (cathode). Also, the kinetic study and the effect of current density and operating time on Cr (VI), turbidity, and chemical oxygen demand (COD) removal efficiency were evaluated. The results show that maximum removal efficiency of 84.7 % for Cr (VI), 88.7 % for turbidity and 81.0 % for COD occurred at a current density of 679.3 A /m2. The maximum turbidity removal value was reached after 15 minutes of operation, while it took 20 minutes to remove the maximum value of Cr (VI) and COD at pH 3.5. The kinetic data were fitted to the pseudo second order model for COD and the pseudo first order for Cr (VI) showing a higher removal rate of Cr than COD. The estimated operating cost was USD 2.74/m3 of effluent. This value only included anode material and energy consumption costs.